2002
DOI: 10.1097/00005768-200201000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the exercise intensity that elicits maximal fat oxidation

Abstract: It is concluded that a protocol with 3-min stages and 35-W increments in work rate can be used to determine Fat(max). Fat oxidation rates are high over a large range of intensities; however, at exercise intensities above Fat(max), fat oxidation rates drop markedly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
496
5
22

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 454 publications
(560 citation statements)
references
References 27 publications
25
496
5
22
Order By: Relevance
“…4 These results have been confirmed in 2002 with men on a cycling ergometer by another group. 5 In contrast to these results, Astorino 6 showed the highest oxidation rate of fat at 75% VO 2 peak in women on a treadmill. VO 2 max of 65 and 75% seem to be too high to burn fat because Van Loon et al 7 found in a further study the highest fat oxidation rate in cycling in well-trained men to be at lower intensities.…”
Section: Introductionmentioning
confidence: 71%
“…4 These results have been confirmed in 2002 with men on a cycling ergometer by another group. 5 In contrast to these results, Astorino 6 showed the highest oxidation rate of fat at 75% VO 2 peak in women on a treadmill. VO 2 max of 65 and 75% seem to be too high to burn fat because Van Loon et al 7 found in a further study the highest fat oxidation rate in cycling in well-trained men to be at lower intensities.…”
Section: Introductionmentioning
confidence: 71%
“…While increasing duration of sub maximal exercise shifts fuel utilization from carbohydrates to lipids (29)(30)(31), fat oxidation also changes as a function of the exercise intensity with a maximum at about 65% of maximum aerobic capability (VO 2max ) (32).…”
Section: Various Other Influences Upon Imcl Levelsmentioning
confidence: 99%
“…Analysis revealed no significant diff erence in fat oxidation rate between Fat max in the Fat max test and the respective constant load test. Therefore, the authors concluded that Fat max tests allow valid determination of Fatmax [ 1 ] . However, the fat oxidation rates in the constant load test were not compared to each other.…”
Section: Limited Benefi T Of Fat Max -Test To Derive Training Prescrimentioning
confidence: 98%
“…To determine Fat max , incremental exercise tests with long stage durations and small increments in work rate have been used. To determine the validation of such Fat max tests, an incremental exercise test was compared to 4-6 continuous prolonged exercise tests at constant work rates, corresponding to the work rates of the incremental exercise test [ 1 ] . Analysis revealed no significant diff erence in fat oxidation rate between Fat max in the Fat max test and the respective constant load test.…”
Section: Limited Benefi T Of Fat Max -Test To Derive Training Prescrimentioning
confidence: 99%
See 1 more Smart Citation